2008
DOI: 10.4304/jcm.3.7.20-27
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of Some RFID Authentication Protocols

Abstract: <p class="MsoNormal" style="text-align: left; margin: 0cm 0cm 0pt; layout-grid-mode: char;" align="left"><span class="text"><span style="font-family: ";Arial";,";sans-serif";; font-size: 9pt;">Two effective attacks, namely de-synchronization attack and impersonation attack, against Ha et al.’s LCSS RFID authentication protocol, Song and Mitchell’s protocol are identified. The former attack can break the synchronization between the RFID reader and the tag in a single protocol run so that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Later, Cao and Shen indicated that Chen et al's scheme cannot resist impersonation attack [15]. Yeh et al further found that Chen et al's scheme cannot protect location privacy and proposed an improvement [14].…”
Section: Introductionmentioning
confidence: 96%
“…Later, Cao and Shen indicated that Chen et al's scheme cannot resist impersonation attack [15]. Yeh et al further found that Chen et al's scheme cannot protect location privacy and proposed an improvement [14].…”
Section: Introductionmentioning
confidence: 96%
“…Cao and Shen [16] found that Chen et al's RFID authentication scheme is vulnerable to impersonation attacks. This study further demonstrates that their scheme does not provide location privacy and suffers from replay attacks.…”
Section: Weaknesses Of Chen Et Al's Schemementioning
confidence: 99%
“…Attackers can record R and h(r) in Step 2 of a legal reading, send malicious queries to cheat the tag out of the responses three times, and then derive the secret value h(TID) È r. After that, attackers can impersonate the tag by using the secret value h(TID) È r and the recorded R and h(r). The detailed attacking steps refer to [16]. Location privacy: If the data transmitted in Step 5 is intercepted or modified, r and r old stored in the server will have been updated while the tag's resident r will not.…”
Section: Weaknesses Of Chen Et Al's Schemementioning
confidence: 99%
“…Currently, secure solutions of the RFID system include: (1) the protocol based on the hash function [2,4,5,6,10,11]; (2) the protocol based on the TEA algorithm [7]; (3) the protocol based on EPC Class 1 Generation 2 standards [1,3,8,13]. The hash-based solutions have become a research hotspot for its simple implementation and stability.…”
Section: Introductionmentioning
confidence: 99%